O mar Cáspio no contexto da política externa da Rússia - Guliyev, Khagani (Hegemonia, 2011)
This study focuses on the question of the role of the Caspian Sea at a large scale in the current Russian foreign policy. It is noted that though in the historical perspective the Caspian Sea basin had been totally dominated by Russia since the beginning of the 19th century, this domination was contested and considerably reduced after the collapse of the Soviet Union. Paradoxically, in parallel for various reasons exposed in the paper, the Caspian Sea gained more importance in the Russian foreign policy giving rise to new challenges for the future of the Russian power in the region.